(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Swami Dayanand Saraswati, the founder of the Arya Samaj, was a pivotal figure in the socio-religious reform movements of 19th-century India. He ardently opposed the practice of untouchability, advocating for social equality and the upliftment of marginalized communities. Dayanand’s reformatory ideas were rooted in his interpretation of Vedic texts, which he believed emphasized the inherent dignity of all human beings. Dayanand's opposition to untouchability stemmed from his belief that all people are descendants of the same divine source. He argued that caste distinctions, particularly those that enforced untouchability, were not supported by the Vedas. In his view, the rigid caste system was a social construct that deviated from the true teachings of Hinduism. He asserted that every individual, regardless of their birth or societal status, possesses an inherent right to dignity and respect. Dayanand's doctrine insisted that adherence to Vedic principles would lead to the abolition of social inequalities, including the banishment of untouchability.